Desempenho de elementos descompactadores para escarificação em sistema de semeadura direta - Bellé, Mateus Potrich (2013)
The competitiveness of the agricultural production system has led producers to seek ways to enhance their crops and increase their profits. With the reduction of sowing windows and intensification of production systems, there was an increase in power, size and frequency of use of equipment at no tillage. These larger and heavier machines brought some system problems, soil compaction by heavy traffic of such equipment. This compaction, in addition to affecting the development of plant roots, increases the strength requirement of implements. Then, the elevation of these levels coupled with stagnation or reduction in production levels that have justified intervention on the system with some type of tillage equipment, and implement that best fits the characteristics of developing a conservation tillage is the chisel plow. The fact that there is a deficiency of comparative information and chisel plow their bodies active, the study aimed to evaluate the performance of three different loosen elements used in chisel plowing (one experimental and two commercial), in order to gather information as a basis to diagnose potential market of loosen experimental elements compared to the loosen commercial elements, using as a benchmark for comparison, the average in strength and power drawbar, area of soil elevation, soil mobilization and swelling, fuel consumption and specific operational fuel consumption and specific operational resistance. Results showed that the experimental loosen element performed better than the commercials on major variables, such as the fuel consumption, average force and power at the drawbar. The presence of the disk in front of the loosen elements damaged the traction force demand, but with lower fuel consumption. The increase in forward speed gave rise to increasing demand for traction force and fuel consumption and reduced specific operational fuel consumption. The slip did not reach the recommended levels in the literature.